The role of the neuronal environment in neurodevelopment and circuit formation in Tuberous Sclerosis Complex - Rocktäschel, P (2023)
Background: Tuberous Sclerosis Complex (TSC) results from TSC1 or TSC2 gene mutations with hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1). TSC is characterised by benign hamartomas in multiple organs including the brain and neurological symptoms are often amongst the most severe and disabling manifestations. Cortical tubers, histologically characterised by disturbed cortical lamination, dysmorphic neurons, and extensive gliosis, are typical brain tumours in TSC that have been implicated in the generation of seizures.